2013
DOI: 10.1155/2013/496138
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Intraoperative Frozen Sections during Thyroid Surgery

Abstract: Objective. To describe the usefulness of intraoperative frozen section in the diagnosis and treatment of thyroid nodules where fine needle aspirate biopsies have evidence of follicular neoplasm. Study Design. Retrospective case series. Methods. All patients have a fine needle aspirate biopsy, an intraoperative frozen section, and final pathology performed on a thyroid nodule after initiation of the Bethesda System for Reporting Thyroid Cytopathology in 2009 at a single tertiary referral center. Sensitivity, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
9
18
0
1
Order By: Relevance
“…This is in line with multiple series in the literature that prove that frozen sections were of little clinical usefulness [18–20]. …”
Section: Discussionsupporting
confidence: 86%
“…This is in line with multiple series in the literature that prove that frozen sections were of little clinical usefulness [18–20]. …”
Section: Discussionsupporting
confidence: 86%
“…Routine intra-operative frozen section biopsy might not be recommended to determine the extent of thyroid surgery. 28,29 32 as seemed to be the case in one patient in the present study who had a positive BRAF result.…”
Section: Resultssupporting
confidence: 76%
“…Routine intra‐operative frozen section biopsy might not be recommended to determine the extent of thyroid surgery . In our series of intra‐operative frozen biopsies ( N =42).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported no clinical usefulness of FS with previous FNA biopsies showing SFM. 26 Additionally, some institutions perform thyroid procedures based on prognostic factors and intraoperative findings regardless of previous FNA results. 20 The diagnosis of SFM is a relatively infrequent diagnosis among the 6 Bethesda categories (,5% of total FNA cases).…”
Section: Discussionmentioning
confidence: 99%